(untitled) (Scottish Archaeological Internet Reports, 2004)
A total of 62 lithics were examined microscopically to determine whether any traces of use wear of evidence or post-depositional movement were apparent. Artefacts comprised blades, flakes, chunks, cores and microliths in a variety of raw materials. Sixty two had traces and this number included unretouched pieces. There are suggestions of spatial diversity across the site: a range of tools were employed in a range of activities.